Cationic polymerization of vinyl monomers using halogen bonding organocatalysts with varied activity. Issue 42 (14th October 2020) - Takagi, Koji; Murakata, Hiroto; Yamauchi, Koji; Hashimoto, Kohei
Abstract : Cationic polymerization of vinyl monomers was investigated using non-ionic and ionic halogen bonding organocatalysts. Abstract : By using non-ionic and multidentate halogen bonding organocatalysts, the cationic polymerization of IBVE was investigated to reveal the relationship between the catalytic activity and the substitution pattern of halogen bond donor units with the aid of theoretical calculation. The polymerization successfully proceeded at room temperature using an appropriate catalyst. The polymerization of other vinyl ethers and styrene derivatives was also investigated in the presence of ionic organocatalysts to figure out that the coordination ability of the counter anion significantly affected the catalytic activity. In particular, the polymerization of pMOS occurred in a controlled manner enabling the molecular weight regulation by ca. Mn = 10 000.